The Aim of Higher Education - Muhammad Jawad Hashim (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of higher education is to nurture higher order thinking. College students attain mastery by acquiring expert ways of thinking. Learning is reflecting. Teachers should aim to stimulate curiosity and a desire to learn. A teacher’s enthusiasm drives learning. Teaching should not cover all topics in the curriculum as this is based on a misperception of the teacher’s role. Teaching is inspiring. Learning during higher education ought to extend beyond discipline-specific expertise to include four higher-order competencies: liberated learning, deep thinking, clear communication, and focused resilience. These in turn, are based on five core skills, namely, writing, numeracy, financial acumen, computing expertise, and design skills. Operationalization of these aims can be achieved via careful course planning, matching assessment to learning goals, and teaching strategies such as Lecture Plus. Lecture Plusis a lecture followed by a learning activity. Learning activities include small-group exercises. Course planning should aim for higher order thinking. Keywords: Education, Graduate; Education, Professional; Teaching Methods